2020
DOI: 10.3390/agriculture10080360
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel QTL for Chlorate Resistance in Rice (Oryza sativa L.)

Abstract: Chlorate resistance analysis is an effective approach commonly used to distinguish the genetic variation between Oryza sativa L. ssp. indica and japonica, and predict the nitrogen use efficiency (NUE). This study aimed at investigating the response of a doubled haploid (DH) population derived from anther culture of 93-11 × Milyang352 exposed to 0.1% potassium chlorate (KClO3) at the seedling stage. The results revealed that the parental rice lines 93-11 (indica) and Milyang352 (japonica) showed distinctive phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…The results revealed that 26 lines and 59 lines carried the indica alleles of NR and NRT, respectively ( Figure S2 ). These introgression lines amplified the expected band size of 200 bp for the indica allele of nitrate reductase, and 165 bp specific to the indica allele of nitrate transporter, respectively, on chromosomes 2 and 10, as reported earlier [ 24 ]. The indica alleles of the NR and NRT were previously suggested to explain the differences in the nitrogen use efficiency between indica and japonica rice varieties.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The results revealed that 26 lines and 59 lines carried the indica alleles of NR and NRT, respectively ( Figure S2 ). These introgression lines amplified the expected band size of 200 bp for the indica allele of nitrate reductase, and 165 bp specific to the indica allele of nitrate transporter, respectively, on chromosomes 2 and 10, as reported earlier [ 24 ]. The indica alleles of the NR and NRT were previously suggested to explain the differences in the nitrogen use efficiency between indica and japonica rice varieties.…”
Section: Resultssupporting
confidence: 77%
“…Prior to germination, rice seeds were sterilized with 0.7% nitric acid (HNO 3 ) (CAS: 7697-37-2, Lot No. 2016B3902; Junsei Chemical Co. Ltd., Tokyo, Japan) overnight to break the dormancy [ 24 ], followed by incubation for 48 h at 27 °C to induce germination. Germinated seeds were grown in 50-well trays containing an enriched soil, and placed in a greenhouse until three-leaf stage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency distribution, the Quantile-Quantile (Q-Q) plots, the correlation between traits, the principal component analysis of all phenotypes of the mapping population, the pairwise kinship matrix [86], and heat map, were generated using the hist, qqplotr, data functions (only for correlation analysis in Microsoft Excel 2016), ggplot2, tidiverse, cluster, and factoextra (for heat map only) R packages in RStudio [87,88].…”
Section: Frequency Distribution Quantile-quantile Plots Correlationmentioning
confidence: 99%